Olfactory processing and odor specificity: a meta-analysis of menstrual cycle variation in olfactory sensitivity - Martinec Nováková Lenka; Havlíček Jan; Roberts S. Craig (Anthropological Review, 2014)
Cycle-correlated variation in olfactory threshold, with women becoming more sensitive to odors mid-cycle, is somewhat supported by the literature but the evidence is not entirely consistent, with several studies finding no, or mixed, effects. It has been argued that cyclic shifts in olfactory threshold might be limited to odors relevant to the mating context.